Geography, economics and political systems: A bird's eye view - Elise S. Brezis; Thierry Verdier (Bar-Ilan University, Department of Economics, 2014)
As early on as in the writings of Montesquieu and Adam Smith, geography plays a preponderant role in explaining disparity of development between nation-states. Smith placed the emphasis on topography, and especially on the role of coasts and rivers in the development of regions. For Montesquieu, climate was an element essential to economic development: His theory asserted that climate may substantially influence the nature and development of human societies. For a long time, economists did not pay attention to geography, and this field was left to sociologists, historians, and geographers. Only lately economists have started analyzing the impact of geography, and this article will examine the various avenues of research that have been taken, wherein the notion of geography mostly encompasses matters related to location, soils, and topography; and yet also climate and epidemiology. The first part focuses on the relationship between geography and economics, while the second part relates geography to political systems and public economics.
Keywords: 330; Politisches System; Wirtschaftswissenschaft; Wirtschaftsgeographie